Exploring 'Unseen' Social Capital in Community Participation Everyday Lives of Poor Mainland Chinese Migrants in Hong Kong - Wong, Sam (ICAS Publications Series, 2007)
This book argues that using social capital to eradicate poverty is less likely to succeed because the mainstream neoinstitutional approach mistakenly assumes that social capital necessarily benefits poor people. This inadequacy calls for a re-assessment of human motivations, institutional dynamics and structural complexity in social capital building. Using ethnographic and participatory methods, this book calls for an exploration of 'unseen' social capital which is intended to challenge the mainstream understanding of 'seen' social capital. As such this book is useful to policy makers and practitioners.